TRADE SECRETS IN THE PERSPECTIVE OF ISLAMIC LAW - Haris, Muhammad; Ridani, Muhammad Noor (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
In business, there must be some information that is confidential, has economic value and is kept confidential by the business owner. This confidential information is called a trade secret. The concept of trade secrets is more related to the legal protection of valuable business information, such as product formulas, product designs, recipes, production methods, or customer data. The method used in this study is the normative legal research method, namely library legal research based on legal materials. The results of this study indicate that Trade Secrets are information that is not known to the public in the field of technology and/or business, has economic value because it is useful in business activities, and is kept confidential by the owner of the Trade Secret. A trade secret will receive protection if it meets the requirements, namely: 1) It is confidential, 2) It has economic value, 3) There are efforts to maintain confidentiality. According to the Islamic view, trade rights, copyright, trade secrets and non-material rights which have economic value are equivalent to material rights which are protected by sharia. Islam really respects and protects property which is a form of a person's ownership. Islam provides protection for individual rights regarding al-mal in the concept of al-masalih al-khamsah (five maslahah that must be safeguarded) which is included in the category of hifdz al-mal (protecting property). This is stated in the holy verses of the Qur'an and authentic hadiths which state that trade secrets are property rights that must be protected, so that anyone who leaks trade secrets to other people is violating the rules of Islam.